Evaluation of integrated modular & traditional curriculum learning environment in medical education - Uzma Kausar; Muhammad Sohail Anjum Noor; Muhammad Usama Sohail; Muhammad Hamza Rana (Journal of University Medical & Dental College, 2024)
ABSTRACT: BACKGROUND & OBJECTIVE: Most medical schools in Pakistan follow a traditional teaching methodology but a newer and refined method named Integrated teaching methodology has been introduced and proven to be more effective than the former method. The study aims to evaluate the pros and cons of integrated modular & traditional curriculum learning environments.METHODOLOGY: A total of 214 students from 1st year and 2nd Year MBBS were enrolled in the study using the convenience sampling technique. 1st Year students were grouped as Group A undergoing an Integrated learning environment and 2nd Year students as Group B undergoing a traditional learning environment at Abwa Medical College, Faisalabad. A pre-validated John Hopkin’s Proforma was distributed to collect data and was analyzed in SPSS 26 using the student’s t-test. The P-value <0.05 was considered as statistically significant.RESULTS: Out of 214, a total of 180 participants recorded their responses. 58% of the total were male and 42% were female. The responses favored the integrated learning environment as it is conducive, supportive, and provides better opportunities in terms of leadership and career options. The curriculum design was also student-centered and designed according to the student's needs as compared to the traditional learning environment. The participants recorded a healthy and positive relationship with the faculty with a statistically significant P-value <0.05.CONCLUSION: The integrated modular system fosters the ability of critical thinking and innovation among students. The curriculum design offers an integrated modular system that is flexible and student-centered which also yields positive outcomes and change among the students.